Synthesis and utilization of polyol-modified high specific surface area Ca(OH)2: an investigation - Yan, Dongjie; Zhu, Yingping; Zhao, Jiaxuan; Zhang, Qian; Wang, Yongping; Yang, Shengjiong (Environmental science and pollution research international, 2024)
Calcium hydroxide (Ca(OH) 2 ) finds widespread use in the petrochemical industry, particularly in flue gas desulfurization applications. However, its conventional usage is limited by its inherently low specific surface area, hampering its efficiency. To address this limitation, this study aims to develop a simple and industrially scalable preparation process for Ca(OH) 2 with a high specific surface area, thereby enhancing its effectiveness in various applications. This study aimed to develop a preparation process for making Ca(OH) 2 with a high specific surface area, suitable for industry and easy to make. Ca(OH) 2 with a specific surface area of 41.555 m 2 /g was successfully synthesized by incorporating polyols during lime digestion. The prepared high specific surface area Ca(OH) 2 is more than five times the specific surface area of ordinary Ca(OH) 2 . Incorporation of polyols within the lime digestion process induces a reduction in both Ca(OH) 2 grain size and particle dimensions, concurrently amplifying the specific surface area and optimizing mass transfer efficiency. Specifically, the desulfurization breakthrough time for Ca(OH) 2 subject to a 15% triethanolamine modification was notably extended to 879 s, surpassing the desulfurization breakthrough time of unaltered Ca(OH) 2 by more than tenfold. Moreover, the modified Ca(OH) 2 exhibited remarkable efficacy in neutralizing acidic wastewater. A new approach for the preparation of high-performance Ca(OH) 2 is proposed in this study, which could facilitate the industrial production of Ca(OH) 2 with high specific surface area.